New nutrition policies for China - Chen, Kevin Z.; Wang, Zimeiyi (Development Initiatives, 2018)
China’s agricultural and economic success has enabled it to supply enough nutritious food for its large population as well as significantly reduce rates of stunting and wasting. However, China still has high levels of undernutrition, with poor regions and vulnerable groups such as children, women, older people and migrants disproportionally affected. The shortage of essential micronutrients also affects millions of Chinese people, and while undernutrition remains a problem, overweight and obesity resulting from excessive saturated fats, calories and/or sugar are increasing at alarming rates. Amid urbanisation, an ageing population and industrialisation, diet-related NCDs such as diabetes are on the rise.